Implementasi Prinsip Komunikasi Islam terhadap Interaksi antar Mahasiswa Program Studi Manejemen Pendidikan Islam Universitas Singaperbangsa Karawang - Kusuma, Adhi; Supriatna, Syakirah Imtinan (Peneliti.net, 2024)
The purpose of this study is to find out the Islamic communication principles used in interaction, as well as the supporting and inhibiting factors that affect the application of Islamic communication principles by students. In addition, this study investigates the types of Islamic communication principles used, as well as how students use them, as well as the supporting and inhibiting factors. This research was conducted through a qualitative approach that uses a descriptive approach. The results of the study showed the following: (1) Islamic communication principles used by students in interacting with each other, such as the principles of honesty, cleanliness, and speaking positively; (2) Students apply Islamic communication principles in interactions with fellow students or in the campus environment by creating good communication, but not all students apply it; (3) Supporting factors in the application of principles, such as good communication skills, positive attitudes, and fair attitudes.